The Impact of Compressor Degradation on The Optimized Fleet Compositions, Optimized Thermal Efficiencies, and The Operations & Maintenance Cost of Fleets of a Reheat Engine Running on Associated Gas Fuel - Mafel Obhuo; Silas O. Okuma; Duabari Silas Aziaka (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Associated gas is a viable source of fuel for industrial gas turbines. Flaring of this fuel resource has not only resulted in environmental pollution and deterioration but also huge energy and economic loss. TURBOMATCH, a Cranfield University performance simulation software was used in modeling a hypothetical but realistic 296MW reheat gas turbine engine.The study was carried out using one clean fleet and three degraded fleets – the optimistic, medium, and pessimistic. Optimization of the fleet compositions and thermal efficiencies were achieved using Genetic algorithm. Detailed operations and maintenance costs analysis for the various fleets were carried out. .Results from the optimization show the optimized fleet compositions, from the various fleets and their turbine entry temperatures for 20 years life span of the project. the result from the 11th to the 20th year of the project, only one unit of engine was left due to engine divestment. Results of the optimized efficiencies for all the fleets show a gradual reduction in optimized efficiencies over the years of the project. Similarly, for all the scenarios considered, from the 11th to the 20th year of the project, with only one unit of engine left, the optimized efficiency trend is observed to be Clean > Optimistic > Medium > Pessimistic.Results from the fleets operations and maintenance costs show that the clean, optimistic, medium, and pessimistic degraded fleets have total operations and maintenance costs to be 1.224, 1.242, 1.265, and 1.297 billion US dollars respectively. Engine degradation resulted to 1.4%, 3.3%, and 5.9% increase in the operations and maintenance costs of the optimistic, medium, and pessimistic degraded fleets respectively.The results, approach and methodology presented in this paper would be a very useful decision-making tool for investors and governments who would want to invest in the economic utilization of associated gas using gas turbines.